Comparison the efficacy of herbal mouthwash with chlorhexidine on gingival index of intubated patients in Intensive Care Unit - Sahra Rezaei; Korosh Rezaei; Mohaddese Mahboubi; Mohammad Hossein Jarahzadeh; Ehsan Momeni; Mostafa Bagherinasab; Mehrdad Gaffari Targhi; Mohammad Reza Memarzadeh (Journal of Indian Society of Periodontology, 2016)
Background: Intubated patients in Intensive Care Unit (ICU) are not able to take care of their mouth health, so they are at risk of bacterial colonization and dental plaques formation that can lead to systemic diseases such as pneumonia and gingivitis. Aims: In randomized, double-blind clinical study, the efficacy of natural herbal mouthwash containing Salvadora persica ethanol extract and Aloe vera gel was compared with chlorhexidine on gingival index (GI) of intubated patients in ICU. Materials and Methods: Seventy-six intubated patients (18–64 years old with mean age 40.35 ± 13.2) in ICU were admitted to this study. The patients were randomly divided into two groups: (1) Herbal mouthwash and (2) chlorhexidine solution. Before the intervention, the GIs was measured by modified GI device into two groups. The mouth was rinsed by mouthwashes every 2–3 h for 4 days. 2 h after the last intervention, GIs were determined. Results: Along with mechanical methods, herbal mouthwash in reducing GI was statistically significant than that of chlorhexidine (P < 0.05). Conclusion: The results of this study introduce a new botanical extract mouthwash with dominant healing effects on GI (1.5 ± 0.6) higher than that of synthetic mouthwash, chlorhexidine (2.31 ± 0.73).